Pembelajaran Kreatif Pendidikan Agama Islam di SMA Negeri 5 Padangsidimpuan untuk Materi Membaca Alquran melalui Metode Puzzle Qira’ati - Ahmad Gozali Harahap (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2022)
Desaign of educational or referred also educational model have the function as a means of measure and control to process studies and lectures in the class. We can conceive if a educator attend into study class without owning what do picture and how do to be done in class, hence to happened the study cannot measure it’s targets.